1996
DOI: 10.1089/hum.1996.7.15-1895
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Antitumor Effects of Killer Cells Induced by Tumor Necrosis Factor Gene-Transduced Autologous Tumor Cells from Gastrointestinal Cancer Patients

Abstract: The purpose of this study was to determine the feasibility of a vaccine therapy using tumor necrosis factor (TNF) gene-transduced autologous tumor cells for the treatment of human gastrointestinal cancers, which tend to have lower immunogenicity than other cancers such as melanoma and renal cell carcinoma. We succeeded in establishing primary cultured tumor cells from 12/54 carcinomatous effusions (4 liver cancer patients, 5 gastric cancer patients, 1 pancreatic cancer patient, and 2 colon cancer patients) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…TNF-secreting tumorcells elicit in the host an antitu mor immune response, involving cytotoxic T lympho cytes (CTLs), natural killer cells, and lymphokine-acti-vated killer cells, capable of eliminating tumors in mouse models. Data consistent with this concept have also been obtained with TNF gene transduced autologous tumor cells from GI cancer patients [55].…”
Section: Gene Augmentationsupporting
confidence: 53%
“…TNF-secreting tumorcells elicit in the host an antitu mor immune response, involving cytotoxic T lympho cytes (CTLs), natural killer cells, and lymphokine-acti-vated killer cells, capable of eliminating tumors in mouse models. Data consistent with this concept have also been obtained with TNF gene transduced autologous tumor cells from GI cancer patients [55].…”
Section: Gene Augmentationsupporting
confidence: 53%
“…The cytotoxic activity of killer cells to nontransduced autologous tumor cells incubated with these TNF gene transfectants was augmented. These and other findings indicate the potential for using TNF gene-transduced tumor cells as a vaccine [113]. Others transfected fibroblasts with the TNF gene and showed that these cells started to produce TNF and had antitumor activities [114].…”
Section: The Promisesmentioning
confidence: 85%
“…We previously reported that the transfection of TNF gene could enhance the expression of MHC class I and ICAM I on tumor cells. 14,15) Then, we examined the expression of surface antigens on double transfectants by flow cytometry. Transfection with IL-12 gene enhanced MHC class I expression and furthermore, slightly enhanced the expression of MHC class II and B7.1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that TNF gene transfection of tumor cells freshly isolated from the ascitic fluids of patients with gastrointestinal cancers enhanced the expression of MHC class I and/or intercellular adhesion molecule-I (ICAM I), and we suggested that this would be involved in augmentation of the killer activity of tumor-infiltrating lymphocytes (TIL) induced by coculturing with autologous tumor cells transfected with TNF gene. 15) On the other hand, IL-12 is a cytokine which potently induces Th1-type cell-mediated immunity 16) and enhances the activities of natural killer T (NKT), 17) NK/ LAK 18) and CTL. 19) Through these immunostimulatory actions, IL-12 is reported to exert potent antitumor and antimetastatic effects via systemic administration 20,21) or upon local production induced by cancer vaccines.…”
mentioning
confidence: 99%